Credit Market in Morocco : A Disequilibrium Approach - Oulidi, Nada (IMF Working Papers; Working Paper, 2009)
In this paper we use a disequilibrium framework common in the 'credit crunch' literature, first to examine whether the slow credit growth in Morocco during the rapid expansion of liquidity in the first half of the decade can be attributed to credit rationing, and second to investigate the role of asset price increases in the recent acceleration of credit growth. Our results do not support the credit rationing hypothesis in the first half of the decade. They do however, show that the recent increase in real estate prices stimulated credit supply and demand, with a stronger effect on the latter.